What Did You Do All Day? Maternal Education and Child Outcomes - Andrabi, Tahir; Das, Jishnu; Khwaja, Asim Ijaz (2012)
Female education levels are very low in many developing countries. Does maternal education have a causal impact on children's educational outcomes even at these very low levels of education? By combining a nationwide census of schools in Pakistan with household data, the authors use the availability of girls' schools in the mother's birth village as an instrument for maternal schooling to address this issue. Since public schools in Pakistan are segregated by gender, the instrument affects only maternal education rather than the education levels of both mothers and fathers. The analysis finds that children of mothers with some education spend 75 minutes more on educational activities at home compared with children whose mothers report no education at all. Mothers with some education also spend more time helping their children with school work; the effect is stronger (an extra 40 minutes per day) in families where the mother is likely the primary care-giver. Finally, test scores for children whose mothers have some education are higher in English, Urdu (the vernacular), and mathematics by 0.24-0.35 standard deviations. There is no relationship between maternal education and mother s time spent on paid work or housework - a posited channel through which education affects bargaining power within the household. And there is no relationship between maternal education and the mother's role in educational decisions or in the provision of other child-specific goods, such as expenditures on pocket money, uniforms, and tuition. The data therefore suggest that at these very low levels of education, maternal education does not substantially affect a mother's bargaining power within the household. Instead, maternal education could directly increase the mother's productivity or affect her preferences toward children s education in a context where her bargaining power is low.